SOSIALISASI PENGGUNAAN APLIKASI PERPUSTAKAAN DIGITAL PADA SMP IT YAABUNAYYA FATHUL KHAER MAKASSAR: Digital Library Application Usage Training - Muhammad Faisal; Ida Ida (Politeknik Negeri Sriwijaya, 2021)
The training activities carried out are expected to improve the quality of library services at partner schools. The goal to be achieved by the author is that each semester can carry out community service to these partners with different training materials. Especially for this semester the author held training on the use of digital library applications. This training is a competency for the academic community in utilizing information and communication technology in increasing reading interest for the academic community. The target of this service activity program is the entire academic community of SMP IT Yaabunayya Fathul Khaer in Makassar City with a total of 50 students, 10 teachers and 1 librarian. The method used is a lecture method, question and answer, and simulation. The results of this activity show: (1) participants (librarian staff) will have knowledge of book data processing, (2) training participants will have knowledge in the borrowing process and (3) training participants will get book information in the library.